2015
DOI: 10.1039/c5sc01838b
|View full text |Cite|
|
Sign up to set email alerts
|

A crystalline sponge based on dispersive forces suitable for X-ray structure determination of included molecular guests

Abstract: A new organic material assembled by dispersive forces exhibits stable one-dimensional channels suitable as the solid support in X-ray structural studies by the crystalline sponge method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…Owing to the removal of the crystallization step from the sequential procedure of single-crystal Xray experiments, considerable attention has been paid to the crystalline sponge method by the communities of organic synthetic chemists, natural product chemists, coordination chemists and crystallographers, as well as researchers in the pharmaceutical, agriculture and food industries. Following our report, the utility of the method has been independently demonstrated by several reports from other groups (Vinogradova et al, 2014;Ramadhar et al, 2015a,b;Sanna et al 2015) in which the crystalline sponge method and related techniques were used to determine the structures of small molecules. Useful applications of this method for absolute structure determination (Yoshioka et al, 2015) and metabolite analysis (Zigon et al, 2015) have been recently reported by our group and others (Kamimura et al, 2013;O'Brien et al, 2014;Tashiro et al, 2012;Kubota et al, 2014;Turega et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…Owing to the removal of the crystallization step from the sequential procedure of single-crystal Xray experiments, considerable attention has been paid to the crystalline sponge method by the communities of organic synthetic chemists, natural product chemists, coordination chemists and crystallographers, as well as researchers in the pharmaceutical, agriculture and food industries. Following our report, the utility of the method has been independently demonstrated by several reports from other groups (Vinogradova et al, 2014;Ramadhar et al, 2015a,b;Sanna et al 2015) in which the crystalline sponge method and related techniques were used to determine the structures of small molecules. Useful applications of this method for absolute structure determination (Yoshioka et al, 2015) and metabolite analysis (Zigon et al, 2015) have been recently reported by our group and others (Kamimura et al, 2013;O'Brien et al, 2014;Tashiro et al, 2012;Kubota et al, 2014;Turega et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…Hence, the NCI approach often does not necessarily require a full DFT calculation 78 and has been successfully applied also to large-scale systems including porous crystalline materials, metal and guest-host complexes, OH-p interactions, and proteins. [78][79][80][81][82][83] Especially regarding repulsive interactions, we would like to point out that care must be taken when using a non-self-consistent density. In a promolecular density there is no Pauli-repulsion between the atomic densities to cause charge depletion.…”
Section: Density Descriptorsmentioning
confidence: 99%
“…However, the potential to inspect unstable moieties or molecules that are not easily crystallised in pure form is highly attractive, and a range of targets has been recently investigated to further demonstrate the utility of the strategy. [54][55][56][57][58][59][60][61] The characterised guest molecules range from simple molecules 54 to reactive acrylate esters 56 and complex Please do not adjust margins Please do not adjust margins molecules with axial and planar chirality, 58 (1R)-(-)-menthyl acetate, 59 α-humulene and its oxidized subproducts. 60 The 'crystalline sponge' approach has also been developed for porous organic materials 61 mirroring studies in MOFs.…”
Section: Mof As Crystallisation Matricesmentioning
confidence: 99%